Analisis Bibliometrik Pengembangan Kompetensi dan Kinerja Aparatur Sipil Negara (ASN) di Indonesia (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study examines the development of scientific publications on the topic of competency development and performance of the State Civil Apparatus (ASN) in Indonesia in the period 2014–2024 using a bibliometric analysis approach. The researcher uses data from scientific articles that have been published and meet the research criteria. Data was obtained from the Google Scholar database with the help of the Publish or Perish application, then analyzed and visualized using VOSviewer to identify publication patterns, research trends, and linkages between topics. From the entire series of article processing processes, 339 scientific publications were identified with a total of 3,460 citations. The results of the analysis show a significant increase in the number of publications, from one publication in 2014 to 103 publications in 2024. The keyword analysis grouped the articles into six main clusters, with the topic "ASN" as the most dominant theme discussed. These findings show increasing academic attention to the development of ASN competencies and performance as an important part of bureaucratic reform, increasing the professionalism of the apparatus, and efforts to improve the quality of public services in Indonesia.